Pelatihan Pembuatan Pupuk Organik (Cair) Berbahan Baku Limbah Rumah Tangga Di Lingkungan Desa Darmaji - Kamil, Insanul; Rosida, Naela; Fadila, Yaniar Asyiah; Putri, Adinda Fitriana; Yulistiani, Linda; Septiana, Tia; Marliani, Nisrina; Putra, Firdaus; Aslam, Firar Bismi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2024)
Environmental problems are still the biggest problem and will never end, especially regarding waste. Where Darmaji Village produces 3,373kg/day of waste. With the large amount of waste produced, people do not know how to process or use the waste. There are many ways to manage and utilize household waste, one of which is making it into liquid organic fertilizer. Using liquid organic fertilizer on plants has the benefit of increasing nitrogen in the soil. In this article, we will discuss a Village Community Empowerment (PMD) activity with training material on Making Liquid Organic Fertilizer (POC) by Utilizing Household Waste.